Reduction of transplant vasculopathy by intraoperative nucleic acid-based therapy in a mouse aortic allograft model - Arif, Rawa; Remes, Anca; Zaradzki, Marcin; Hecker, Markus; Karck, Matthias; Wagner, Andreas H. (The thoracic and cardiovascular surgeon, 2019)
Transplant vasculopathy (TV) is the main limiting factor for long-term graft survival characterized by fibrosis, myofibroblast, and smooth muscle cell (SMC) proliferation. Decoy oligodeoxynucleotide (dODN) against the transcription factor activator protein-1 (AP-1) might interfere with the expression of AV-related genes that govern neointima formation.